Flexible insurance for heterogeneous farmers: Results from a small-scale pilot in Ethiopia - Hill, Ruth Vargas; Robles, Miguel (International Food Policy Research Institute, 2011)
We analyze the effectiveness of a new approach in providing weather index-based insurance products to low-income populations. The approach is based on the concept of providing multiple weather securities that pay a fixed amount if the event written on the security (that monthly rainfall at a nearby weather station falls below a stated cutoff) comes true. A theoretical model is developed to outline the conditions in which weather securities could outperform crop-specific weather index-based insurance policies. Data collected during both an experimental game and real purchases of such insurance policies among farmers in southern Ethiopia suggest that the securities are well understood and can fit heterogeneous farmer needs. This paper documents (1) heterogeneity of rainfall risk among farmers, (2) the understanding of securities and transmission of information about weather securities among members of endogenously formed risk-sharing groups, and (3) the nature of purchasing decisions and manner in which they are made.